A survey of methods used by Malaysian brokerage firm investment analysts to appraise investments in ordinary shares - Ramadilli Mohd, Shamsher Mohamad; Md Nassir, Annuar (Universiti Putra Malaysia Press, 1997)
This study provides a broad description of the methods used by investment analysts attached to brokerage houses in Malaysia to appraise investments in the ordinary shares of companies. Fifty-seven investment analysts were sampled from all the brokerage houses in Malaysia and a mail questionnaire method was used to solicit the required information. The findings suggest that the sampled analysts used a combination of methods to assess the value of shares, though the emphasis is on the fundamental analysis. They use a three-year earnings forecast period, prefer accrual earnings to cashflows and use a variety of sources of information with the emphasis on financial information from audited financial statements. substantiated by qualitative information gathered through company visits. In general, though the findings are inconclusive regarding the most common methods used for share price valuation, the inclination is towards the earnings multiplier approach.